Isotopic niches of fin whales from the Mediterranean Sea and the Celtic Sea (North Atlantic). (June 2017) - Das, Krishna; Holleville, Ophélie; Ryan, Conor; Berrow, Simon; Gilles, Anita; Ody, Denis; Michel, Loïc N.
Abstract: The fin whale ( Balaenoptera physalus ) is the most abundant and widespread mysticete species in the Mediterranean Sea, found mostly in deep, offshore waters of the western and central portion of the region. In the Mediterranean, this species is known to feed mainly on krill, in contrast to its Atlantic counterpart, which displays a more diversified diet. The International Whaling Commission recognizes several managements units in the Atlantic and the Mediterranean Sea and the connectivity between these populations is still being debated. Questions remain about inter-individual feeding strategies and trophic ecology. The goal of this study was to compare isotopic niches of fin whales from the Mediterranean Sea and the Celtic Sea (North Atlantic). δ 13 C and δ 15 N values were analysed in 136 skin biopsies from free-ranging Mediterranean fin whales sampled in 2010 and 2011 during campaigns at sea. δ 13 C and δ 15 N values ranged from −20.4 to −17.1‰ and from 5.9 to 8.9‰, respectively. These values are in good agreement with those estimated previously from baleen plates from Mediterranean and North Atlantic fin whales. The narrow isotopic niche width of the Mediterranean fin whale (Standard Ellipses area SEAc) compared to the North Atlantic fin whale raises many concerns in the context of global changes and long-term consequences. One could indeed expect that species displaying narrow niches would be more susceptible to ecosystem fragmentation and other anthropogenic impacts. Highlights: δ 13 C and δ 15 N were determined in the skin of 136 free-ranging fin whales from the Mediterranean Sea. Isotopic niches (SIBER model) were estimated for Mediterranean and Celtic Sea fin whales. Data revealed a narrow isotopic niche width of the Mediterranean whales compared to Celtic ones. Findings raise many concerns in the context of global changes.